The application of the right to freedom of expression in demonstration based on principles of a democratic state - Sofwan, Edi; Sopiyana, Muhammad; Fathurrahman, Ali Masykur (Universitas Negeri Yogyakarta, 2022)
Expressing opinions in demonstration is a right that has been guaranteed in the constitution and law. The arrangement is written in the 1945 Constitution of the Republic of Indonesia Article 28E paragraph (3) and Law Number 9 of 1998 concerning the freedom to express opinion in public. A democratic country has a great respect for differences of opinion manifested in the form of demonstration. However, the freedom of demonstration is in the form of responsible freedom regulated in Article 6 of Law No. 9 of 1998. In this demonstration, the actions must respect the rights of others, so that no one is harmed by the demonstration. If someone is harmed, they must prioritize the principles of justice in accordance with applicable law. This study was conducted with a qualitative method approach, namely by using the type of normative research, by conducting a study of legislation (Statute approach). This study resulted that the demonstration arrangements regulated in the law must be respected by all parties, where the principle of legal protection is attached to demonstration participants and security forces to respect each other's democratic values in Indonesia. Furthermore, on the principle of right to freedom of expression in a democratic country, all citizens must have the same rights in any form of expression. If there is a party who is harmed, it must be resolved according to the applicable law, so that the Indonesian guarantee legal certainty from irresponsible parties to uphold democratic values, as well as freedom of opinion.